The mechanistic immunosuppressive role of the tumour vasculature and potential nanoparticle-mediated therapeutic strategies - Ileiwat, Zakaria Elias; Tabish, Tanveer A.; Zinovkin, Dmitry A.; Yuzugulen, Jale; Arghiani, Nahid; Pranjol, Md Zahidul I. (Frontiers in Immunology, 2022)
The tumour vasculature is well-established to display irregular structure and hierarchy that is conducive to promoting tumour growth and metastasis while maintaining immunosuppression. As tumours grow, their metabolic rate increases while their distance from blood vessels furthers, generating a hypoxic and acidic tumour microenvironment. Consequently, cancer cells upregulate the expression of pro-angiogenic factors which propagate aberrant blood vessel formation. This generates atypical vascular features that reduce chemotherapy, radiotherapy, and immunotherapy efficacy. Therefore, the development of therapies aiming to restore the vasculature to a functional state remains a necessary research target. Many anti-angiogenic therapies aim to target this such as bevacizumab or sunitinib but have shown variable efficacy in solid tumours due to intrinsic or acquired resistance. Therefore, novel therapies such as those integrating nanotechnology may provide alternatives to overcoming the barriers generated by the tumour vasculature. This review summarises the mechanisms that induce abnormal tumour angiogenesis and how the vasculature’s features elicit immunosuppression. Furthermore, the review explores examples of current and novel treatments that target the tumour vasculature.